1986
DOI: 10.1111/j.1558-5646.1986.tb05724.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INHERITANCE OF COURTSHIP BEHAVIOR AND ITS ROLE AS A REPRODUCTIVE ISOLATING MECHANISM IN TWO SPECIES OFSCHIZOCOSAWOLF SPIDERS (ARANEAE; LYCOSIDAE)

Abstract: The courtship behaviors of two morphologically similar spider species, Schizocosa ocreata and S. rovneri, are distinctive and prevent interbreeding. We used “forced” copulation between these species to investigate the mode of inheritance of the courtship behavior and to determine whether postmating isolating mechanisms exist. F1 hybrids proved to be behaviorally sterile, but they were capable of producing viable offspring when forced to interbreed. Analysis of the courtship behaviors of F1, F2, and backcross p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 38 publications
1
80
0
2
Order By: Relevance
“…), lacks decorative foreleg tufts and the conspicuous leg-tapping display involved in the courtship of its congener. It does, however, exhibit a body "bounce," in which it thrusts the abdomen and cephalothorax against the substratum and simultaneously produces a vibratory signal via palpal stridulation (Uetz and Denterlein, 1979;Stratton and Uetz, 1981, 1983, 1986. Female S. rovneri respond receptively more often to conspecific male vibration signals than visual cues.…”
Section: Study Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…), lacks decorative foreleg tufts and the conspicuous leg-tapping display involved in the courtship of its congener. It does, however, exhibit a body "bounce," in which it thrusts the abdomen and cephalothorax against the substratum and simultaneously produces a vibratory signal via palpal stridulation (Uetz and Denterlein, 1979;Stratton and Uetz, 1981, 1983, 1986. Female S. rovneri respond receptively more often to conspecific male vibration signals than visual cues.…”
Section: Study Speciesmentioning
confidence: 99%
“…(1) Schizocosa ocreata (Hentz) has decorative tufts of dark bristles on the forelegs as well as a highly visual and locomotive courtship display, which involves conspicuous tapping of the tufted forelegs and stridulation with the pedipalps (Uetz and Denterlein, 1970;Stratton and Uetz, 1981, 1983, 1986. Females of this species exhibit receptivity with equal frequency to isolated visual and vibratory courtship signals from conspecific males (Scheffer et al, 1996).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate behavioral phenotypes are common in species hybrids and have been found for a variety of traits, including migratory behavior in birds (Helbig, 1991) and courtship behavior in birds (Ficken and Ficken, 1968) and spiders (Stratton and Uetz, 1986). Pioneering work by Shaw (1996Shaw ( , 2000 characterized the quantitative genetic basis of differences in male courtship song and female preferences among species in the cricket genus Laupala.…”
Section: Genetic Basis Of Courtship Differences Between Speciesmentioning
confidence: 99%
“…In these potentially cannibalistic species, such as some spiders, the efficacy of courtship signals is presumed to be subject to high selection pressures, thus making spiders ideal organisms for studies of sexual selection. The importance of specific species recognition signals in spider courtship displays has been demonstrated by several studies (Stratton & Uetz 1981, 1983, 1986Uetz & Stratton 1982), while others have shown the importance of female choice (Jackson 1977;Watson 1991Watson , 1993Clark & Uetz 1992;Scheffer et al 1996;McClintock & Uetz 1996). However, the selective pressures acting upon the evolution of these signals are not necessarily mutually exclusive.…”
mentioning
confidence: 99%